Analisis Pengendalian Kualitas Produk dengan Menggunakan Metode Statistical Quality Control (SQC) : (Studi Kasus pada PD. Penggergajian Kayu Ciawi Putra di Kabupaten Tasikmalaya) - Silvia Intan Suviatna; Rita Tri Yusnita; Depy Muhamad Pauzy (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the level of damage to a product, identify the factors that cause damage, and recommend corrective action (Case study of PD.Ciawi Putra Timber Sawmill). The research method used consists of collecting data through observation and interviews, the steps include using Check Sheet tools, Control Maps, Pareto Diagrams, Cause-Effect Diagrams. The results of the analysis using a cause and effect diagram show that the causes of poor wooden pallets are labor, methods, materials and machines. The Pareto diagram shows that the type of product damage is more dominant in blackish defects amounting to 458 units or 50.39% and is dominated by three types of damage, namely Cracked Defect Type, Blackish Defect Type and Imprecise Form Defect Type. The results of the control map analysis show that PD quality control. The Ciawi Putra Sawmill is still not under control. The next step to reduce the risk of product losses is to create Standard Operating Procedures (SOP).